The COVID‐19 pandemic and associated declines in cancer incidence by race/ethnicity and census‐tract level SES, rurality, and persistent poverty status - Benmei Liu; Mandi Yu; Jeffrey Byrne; Katheen A. Cronin; Eric J. Feuer (Cancer Medicine)
Abstract Background The COVID‐19 pandemic had a significant impact on cancer screening and treatment, particularly in 2020. However, no single study has comprehensively analyzed its effects on cancer incidence and disparities among groups such as race/ethnicity, socioeconomic status (SES), persistent poverty (PP), and rurality. Methods Utilizing the recent data from the United States National Cancer Institute's Surveillance, Epidemiology, and End Results Program, we calculated delay‐ and age‐adjusted incidence rates for 13 cancer sites in 2020 and 2015–2019. Percent changes (PCs) of rates in 2020 compared to 2015–2019 were measured and compared across race/ethnic, census tract‐level SES, PP, and rurality groups. Results Overall, incidence rates decreased from 2015–2019 to 2020, with varying PCs by cancer sites and population groups. Notably, NH Blacks showed significantly larger PCs than NH Whites in female lung, prostate, and colon cancers (e.g., prostate cancer: NH Blacks −7.3, 95% CI: [−9.0, −5.5]; NH Whites: −3.1, 95% CI: [−3.9, −2.2]). Significantly larger PCs were observed for the lowest versus highest SES groups (prostate cancer), PP versus non‐PP groups (prostate and female breast cancer), and all urban versus rural areas (prostate, female breast, female and male lung, colon, cervix, melanoma, liver, bladder, and kidney cancer). Conclusions The COVID‐19 pandemic coincided with reduction in incidence rates in the U.S. in 2020 and was associated with worsening disparities among groups, including race/ethnicity, SES, rurality, and PP groups, across most cancer sites. Further investigation is needed to understand the specific effects of COVID‐19 on different population groups of interest.